Moisture sorption isotherm and thermodynamic properties of jamun (Syzygium cumini L.) powder made from jamun pulp and seed - Indira Dey Paul; Madhusweta Das (International Journal of Food Studies)
The present work aimed to: i) find the suitable proportion, based on sensory evaluation, of microwave-convective hot air dried jamun (Syzygium cumini L.) pulp and seed kernel powder to be mixed for the preparation of jamun powder (JP); ii) generate and model the moisture sorption isotherm (MSI) of JP; and iii) estimate net isosteric heat of sorption (qst), spreading pressure (Φ), net integral enthalpy (Qin), and net integral entropy (Sin). To formulate JP, the proportion (w/w, db) comprising 2% kernel and 98% pulp powder was the most desirable. The Peleg model was the best fit to MSI of JP. The qst decreased following linear relationship from 11.02 kJ. mol−1 at 5% equilibrium moisture content (EMC) to 0.27 kJ. mol−1 at 30% EMC. The Φ increased with increase in water activity and decreased with increase in temperature from 25 oC to 35 oC, and the values of Φ at 45 oC were even higher than at 25 oC. Net integral enthalpy (Qin) initially decreased till 6% moisture content in JP and displayed an increasing trend with further increase in moisture content. On the contrary, Sin kept on decreasing continually with increasing moisture content. The moisture zone of 7-11% was considered safe for storage of JP within the temperature range of 45-25 oC.